“The German Saver” and the Low Policy Rate Environment - Reint E. Gropp; Vahid Saadi (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
It is widely claimed that “the German saver” suffers (i.e. generates significantly lower returns on her savings) in the low interest environment that Germany currently experiences relative to a high interest rate environment. With “low interest rate environment”, the observers tend to mean “low policy rates”, i.e. the European Central Bank's (ECB) main refinancing rate.
urn:nbn:de:gbv:3:2-48517
Keywords: 330; European Union; German saver; Low Policy Rate Environment